A Critical Assessment of the Scientific Basis, and Implementation, of Regulations for the Safety Assessment and Marketing of Innovative Tobacco-related Products. Issue 4 (September 2015) - Combes, Robert D.; Balls, Michael
Our scientific, logistical, ethical and animal welfare-related concerns about the latest US Food and Drug Administration (FDA) regulations for existing and so-called 'new' tobacco products, aimed at reducing harmful exposures, are explained. Such claims for sales in the USA now have to be based on a wide range of information, a key part of which will increasingly be data on safety and risk. One of the path-ways to achieve marketing authorisation is to demonstrate substantial equivalence (SE) with benchmark products, called predicates. However, the regulations are insufficiently transparent with regard to: a) a rationale for the cut-off date for 'old' and 'new' products, and for exempting the former from regulation; b) the scientific validity and operation of SE; c) options for product labelling to circumvent SE; d) the experimental data required to support, and criteria to judge, a claim; and e) a strategy for risk assessment/management. Scientific problems related to the traditional animal methods used in respiratory disease and inhalation toxicology, and the use of quantitative comparators of toxicity, such as the No Observed Adverse Effect Level, are discussed. We review the advantages of relevant in vitro, mechanism-based, target tissue-oriented technologies, which an advisory report of the Institute of Medicine of the US National Academy of Sciences largely overlooked. These benefits include: a) the availability, for every major site in the respiratory tract, of organotypic human cell-based tissue culture systems, many of which are already being used by the industry; b) the accurate determination of concentrations of test materials received by target cells; c) methods for exposure to particulate and vapour phases of smoke, separately or combined; d) the ability to study tissue-specific biotransformation; and e) the use of modern, human-focused methodologies, unaffected by species differences. How data extrapolation, for risk assessment, from tissue culture to the whole animal, could be addressed, is also discussed. A cost (to animal welfare)–benefit (to society, including industry and consumers) analysis was conducted, taking into account the above information; the potential for animal suffering; the extensive data already available; the existence of other, less hazardous forms of nicotine delivery; the fact that much data will be generated solely for benchmarking; and that many smokers (especially nicotine-dependents) ignore health warnings. It is concluded that, in common with policies of several tobacco companies and countries, the use of laboratory animals for tobacco testing is very difficult, if not impossible, to justify. Instead, we propose and argue for an integrated testing scheme, starting with extensive chemical analysis of the ingredients and byproducts associated with the use of tobacco products and their toxicity, followed by use of in vitro systems and early clinical studies (involving specific biomarkers) with weight-of-evidence assessments at each stage. Appropriate adjustment factors could be developed to enable concentration–response data obtained in vitro, with the other information generated by the strategy, to enable the FDA to meet its objectives. It is hoped that our intentionally provocative ideas will stimulate further debate on this contentious area of regulatory testing and public safety.